Tombes à fossé circulaire et chemins de la fin du premier âge du Fer à la Pailletrice, ZAC du Parc de l’Aéroport à Pérols (Hérault) : nouvelles données sur les pratiques funéraires protohistoriques des plaines languedociennes - Isabelle Daveau; Bernard Dedet (Gallia)
Graves dating from the Middle Iron Age in the Languedocian plains remain little known. The preventive excavation conducted in 2004 at la Pailletrice in Pérols, close to Montpellier, uncovered four graves with circular pits from the end of the 6th c. BC and the early 5th c. BC. They are gathered next to a stone path, testified from the last quarter of the 6th c. BC. For the first time in this area, the vestiges have been preserved enough to assess the funerary characteristics of such circular pits. The best preserved monument shows a peripheral ditch marking out a very low earth barrow with a secondary cremation deposit next to its centre, an ossuary with the remains of two bronze vases, and a shallow pit containing residues from the pyre. A series of amphorae and drinking vessels remains have been preserved in all these pits, likely proof of rituals performed next to the graves. The data these vestiges revealed is then integrated within the context of funerary practices during the first Iron Age in eastern Languedoc.